PENGARUH PUPUK NITROGEN TERHADAP PENAMPILAN DAN PRODUKTIVITAS PADI INPARI SIDENUK - Syakhril, Riyanto, dan Halda Arsyad (Universitas 17 Agustus 1945 Samarinda, 2014)
The objective of the experiment were to know the performance and productivity of Inpari Sidenuk Variety. The experiment was conducted in Rempanga Village, Loa Kulu District, Kutai Kartanegara Regency. The seedlings at 21 days old were planted by jajar legowo method (2:1) with plant spacing 40 cm x 20 cm x 10 cm. The numbers of seedling per hill was one plant. All paddy plants were fertilized by 400 kg Pelangi Prima compound (20-10-10) per ha at 1 week after planting. Nitrogen fertilizer was given 40 days after planting, where previously examined leaf colour with leaf colour chart. The treatment of nitrogen fertilizer consists of two level i.e without fertilizer (N0) and 125 kg ha-1 (N1). Observed variabel include plant height 28 DAP and harvest time, total number of tiller at 28 DAP and harvest time, number of productive tillers, panicle length, number of grains per panicle, percentage of filled grain, 1.000 grain weight, and yields.T test was used to analyze the data, except for the yield. The results show that N1 treatment have significant effect on plant height at harvest time, panicle length, 1.000 grain weight. While its effect on yield was 7.52 tonnes ha-1.